2020
DOI: 10.2478/sjph-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Croatian Version of Work Ability Index (WAI) in Population of Nurses on Transformed Item-Specific Scores

Abstract: AimTo assess the psychometric properties of the Croatian version of a Work Ability Index Questionnaire (WAIQ-CRO) in the population of nurses by using a specific methodological approach.MethodsA cross-sectional survey was conducted in a sample of 711 Croatian nurses in 2018 in Zagreb, Croatia. The instrument’s internal consistency was assessed by using Cronbach’s alpha coefficient (α). The factor structure was verified by confirmatory (CFA) and exploratory factor analysis (EFA), with the assumption of a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Detailed description of the instrument and scoring is provided elsewhere ( 3 ). In our study the Croatian version of a WAIQ (WAIQ-CRO) was used, which demonstrated satisfactory internal consistency (Cronbach’s α=0.71) and a three-factor structure ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed description of the instrument and scoring is provided elsewhere ( 3 ). In our study the Croatian version of a WAIQ (WAIQ-CRO) was used, which demonstrated satisfactory internal consistency (Cronbach’s α=0.71) and a three-factor structure ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The values obtained using the WAI method were compared with the reference value of foreign studies; e.g., (Ilmarinen et al 1997;Ilmarinen 2009;Karazman et al 1999;Smrekar et al 2019), which represent the average value of work ability for categories of men and women of the same age and performing the identical type of work. As mentioned, the work ability resulting value was measured at a value of 42.8 rendering that the examined company disposes of relatively good work ability needed to be maintained.…”
Section: Qualitative Research-application Of Work Ability Indexmentioning
confidence: 99%
“…After this phase, another crossroad in the workflow emerges-a personal development and risk of unemployment together with the round-the-clock care and support of the family. The final stage is usually characterized by oncoming retirement from the labor market, which may be caused either by company's strategy, or worker's individual plan (Kröll et al 2017;Smrekar et al 2019;Verheyen et al 2016).…”
Section: Introductionmentioning
confidence: 99%